Role Central-Local Governance in Stakeholder Analysis of Social Protection Policy in Tanjungpinang City - Margaretha, Rita; Mahadiansar, Mahadiansar (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
The Government continues to focus on handling Indonesia's pandemic and social protection programs. Limiting activities has succeeded in suppressing people's mobility, so daily Covid-19 cases are starting to decline. Various policy adjustments through the APBN instrument have also been carried out quickly to protect the public, handle the spread of Covid-19 and protect the community from a social and economic perspective. A research method is a qualitative approach using existing secondary data that the researcher considers relevant and essential to be studied and analyzed in depth. Secondary data has been processed first and only obtained by researchers from other sources as additional information. Some secondary data sources are books, journals, government publications, websites, or other supporting sources. The data analysis technique is analyzed using logic triangulation and investigator triangulation methods. The study results show that in Indonesia's social protection policies during the COVID-19 pandemic, there is a gap between the central Government and local governments. In addition, stakeholders focus on long-term programs prepared to overcome the social inequality in the people of Tanjungpinang city. In addition, researchers also found that the social protection policy programs carried out by stakeholders in the city of Tanjungpinang have met the community's needs during the covid 19 pandemic. Several innovations evidence this, and social protection policies are carried out by the central Government to local governments so that each stakeholder can implement these programs in the future.